Pricing joint use of municipal services : theoretical perspectives and regulatory issues - Valkama, Pekka; Bailey, Stephen J. (John Wiley & Sons, 2018)
This paper analyses price regulation of inter-municipal contracts in Finland to demonstrate interpretative problems of regulatory rules specifying full-cost or market prices and, by so doing, deepen understanding of the theoretical underpinnings for pricing collaborative municipal services. It considers how to price inter-municipal services taking into account the specific socio-economic nature of inter-municipal cooperation, including both financial and non-financial objectives, through a new joint-use pricing model of municipal services that challenges the supremacy of full-cost pricing requirements in cases of inter-municipal collaborative contracting. Acknowledging limitations and benefits, it concludes European Single Market rules militate against municipal discretion and localism.
Keywords: full-cost pricing; inter-municipal contracting; joint use; market pricing; public procurement; fi=Johtaminen ja organisaatiot|en=Management and Organization|